FACTORS CONTRIBUTING TO THE EMERGENCE OF CORRUPTION RISKS IN THE FIELD OF HIGHER EDUCATION (Scientific journal of the Fergana State University, 2026)
About the factors of corruption that can occur in all state, non-state and foreign higher education institutions in the territory of our republic, and effective ways to fight against them.